Therapeutic Role of Protein Tyrosine Phosphatase 1B in Parkinson’s Disease via Antineuroinflammation and Neuroprotection In Vitro and In Vivo - Chien-Wei Feng; Nan-Fu Chen; Te-Fu Chan; Wu-Fu Chen (Parkinson's Disease)
Parkinson’s disease (PD) is one of the most widespread neurodegenerative diseases. However, the currently available treatments could only relieve symptoms. Novel therapeutic targets are urgently needed. Several previous studies mentioned that protein tyrosine phosphatase 1B (PTP1B) acted as a negative regulator of the insulin signal pathway and played a significant role in the inflammation process. However, few studies have investigated the role of PTP1B in the central nervous system. Our study showed that suramin, an inhibitor of PTP1B, could improve neuronal damage. It could significantly attenuate the interferon-gamma-induced upregulation of proinflammatory cytokines, including inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB). It enhanced M2 type microglia markers, such as arginase-1 and Ym-1 in BV2 murine microglial cells. PTP1B inhibition also reversed 6-hydroxydopamine- (6-OHDA-) induced downregulation of phospho-cAMP response element-binding protein (p-CREB) and brain-derived neurotrophic factor (BDNF) in SH-SY5Y cells. Besides, we knocked down and overexpressed PTP1B in the SH-SY5Y cells to confirm its role in neuroprotection. We also verified the effect of suramin in the zebrafish PD model. Treatment with suramin could significantly reverse 6-OHDA-induced locomotor deficits and improved tyrosine hydroxylase (TH) via attenuating endoplasmic reticulum (ER) stress biomarkers. These results support that PTP1B could potentially regulate PD via antineuroinflammation and antiapoptotic pathways.